2013
DOI: 10.1177/0883073813509887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Youth Football on Selected Clinical Measures of Neurologic Function

Abstract: We assessed 10 youth football players (13.4 ± 0.7 y) immediately before and after their season to explore the effects of football participation on selected clinical measures of neurologic function. Postseason postural stability in a closed-eye condition was improved compared to preseason (P = .017). Neurocognitive testing with the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) battery revealed that reaction time was significantly faster at postseason (P = .015). There were no significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Controls were in place to examine the potential role for fatigue or other factors related to play/practice on test scores in the absence of concussion. Previous studies of the K-D test have demonstrated that vigorous exercise/scrimmage alone is associated with improvements in scores, consistent with learning effects inherent in performance measures in the absence of injury (15,17).…”
Section: Study Participantsmentioning
confidence: 61%
See 3 more Smart Citations
“…Controls were in place to examine the potential role for fatigue or other factors related to play/practice on test scores in the absence of concussion. Previous studies of the K-D test have demonstrated that vigorous exercise/scrimmage alone is associated with improvements in scores, consistent with learning effects inherent in performance measures in the absence of injury (15,17).…”
Section: Study Participantsmentioning
confidence: 61%
“…Higher testing times compared with baseline indicate worsening of performance. Worsening scores are not observed after competition/fatigue alone (15); healthy athletes typically show improvement with exercise (15,17). Because shorter times are expected in nonconcussed athletes, any worsening of K-D scores from baseline is consistent with concussion.…”
Section: King-devick Testmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, there is mixed consensus regarding reported neuropsychological test results, as typified by reaction time measures and neuropsychological testing following exposure to subconcussive head blows in sports; for example, in adolescent sports (soccer and football), some authors report no measurable difference, [41][42][43][44][45][46][47] while others report changes following chronic HIE. [48][49][50][51][52][53] These disparities invite further debate regarding the value of such tests.…”
Section: Neuropsychological Testing Batterymentioning
confidence: 99%